Epigenetically silenced lncRNA SNAI3-AS1 promotes ferroptosis in glioma via perturbing the m6A-dependent recognition of Nrf2 mRNA mediated by SND1 - Jianglin Zheng; Qing Zhang; Zhen Zhao; Yue Qiu; Yujie Zhou; Zhipeng Wu; Cheng Jiang; Xuan Wang; Xiaobing Jiang (Journal of Experimental & Clinical Cancer Research, 2023)
Abstract Background Ferroptosis has been linked to tumor progression and resistance to antineoplastic therapy. Long noncoding RNA (lncRNA) exerts a regulatory role in various biological processes of tumor cells, while the function and molecular mechanism of lncRNA in ferroptosis are yet to be clarified in glioma. Methods Both gain-of-function and loss-of-function experiments were employed to investigate the effects of SNAI3-AS1 on the tumorigenesis and ferroptosis susceptibility of glioma in vitro and in vivo. Bioinformatics analysis, Bisulfite sequencing PCR, RNA pull-down, RIP, MeRIP and dual-luciferase reporter assay were performed to explore the low expression mechanism of SNAI3-AS1 and the downstream mechanism of SNAI3-AS1 in ferroptosis susceptibility of glioma. Results We found that ferroptosis inducer erastin downregulates SNAI3-AS1 expression in glioma by increasing the DNA methylation level of SNAI3-AS1 promoter. SNAI3-AS1 functions as a tumor suppressor in glioma. Importantly, SNAI3-AS1 enhances the anti-tumor activity of erastin by promoting ferroptosis both in vitro and in vivo. Mechanistically, SNAI3-AS1 competitively binds to SND1 and perturbs the m6A-dependent recognition of Nrf2 mRNA 3’UTR by SND1, thereby reducing the mRNA stability of Nrf2. Rescue experiments confirmed that SND1 overexpression and silence can rescue the gain- and loss-of-function ferroptotic phenotypes of SNAI3-AS1, respectively. Conclusions Our findings elucidate the effect and detailed mechanism of SNAI3-AS1/SND1/Nrf2 signalling axis in ferroptosis, and provide a theoretical support for inducing ferroptosis to improve glioma treatment.